The trends of modeling the ways of formation, distribution and exploitation of megapolis lands using geo-information systems - Mamonov, Kostyantyn; Shipulin, Volodymyr; Shterndok, Ernest (Human Geography Journal, 2017)
The areas of need for ways of modeling the formation, distribution and use of land metropolis using GIS are identified. The article is to define the areas of modeling ways of formation, distribution and use of land metropolis using GIS. In the study, the following objectives are set: to develop an algorithm process data base (Data System) creation for pecuniary valuation of land settlements with the use of GIS; to offer process model taking into account the influence of one factor modules using geographic information systems; to identify components of geo providing expert money evaluation of land metropolis; to describe the general procedure for expert money assessment of land and property by using geographic information system software; to develop an algorithm methods for expert evaluation of land. Identified tools built algorithms used for modeling the ways of formation, distribution and use of land metropolis using GIS. Directions ways of modeling the formation, distribution and use of land metropolis using GIS.